2017
DOI: 10.4047/jap.2017.9.5.350
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of composite resin to high performance polymer PEKK according to surface treatments and bonding materials

Abstract: PURPOSEThe object of the present study was to evaluate the shear bonding strength of composite to PEKK by applying several methods of surface treatment associated with various bonding materials.MATERIALS AND METHODSOne hundred and fifty PEKK specimens were assigned randomly to fifteen groups (n = 10) with the combination of three different surface treatments (95% sulfuric acid etching, airborne abrasion with 50 µm alumina, and airborne abrasion with 110 µm silica-coating alumina) and five different bonding mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 22 publications
3
61
0
Order By: Relevance
“…In a comparable study, adhesives with multifunctional methacrylates such as Luxatemp Glaze & Bond showed TBS values of 15.0 MPa after 3 days storage and 12.9 MPa after 150 days storage 23) . A study by Lee et al 25) showed SBS values at 14.45 MPa. However, these values were achieved without artificial aging by thermal cycling.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a comparable study, adhesives with multifunctional methacrylates such as Luxatemp Glaze & Bond showed TBS values of 15.0 MPa after 3 days storage and 12.9 MPa after 150 days storage 23) . A study by Lee et al 25) showed SBS values at 14.45 MPa. However, these values were achieved without artificial aging by thermal cycling.…”
Section: Discussionmentioning
confidence: 95%
“…All previous studies agree that an increase in surface roughness is necessary to achieve better wettability 11,[16][17][18][19] and additional bonding is necessary. Some studies are therefore focusing on different surface treatments 11,[16][17][18][20][21][22][23] and others on bonding agents [23][24][25] to produce a durable bond.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both the post-surface treatment and the cement should be appropriately chosen to achieve a durable bond strength when using PEKK as a post material. Few studies have suggested different surface treatment methods to increase the bond strength of PEKK such as the combination of silica coating and an adhesive primer or the combination of air abrasion and an adhesive primer [ 27 , 28 ]. There has been only one study that performed tensile bond strength tests to evaluate the bond strength between PEKK and resin cements [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high adhesion of a metal layer is supported by a micro structure on the surface. This can be realized by plasma etching, chemical etching, laser etching or mechanical etching, e.g., with sandblasting [24][25][26]. There are other processes in use, but all of them require an additional processing step.…”
Section: Introductionmentioning
confidence: 99%